Nursing Performance in Preventing Adverse Health Events: A Literature Review - , Simone Ribeiro Vieira Borges, Edileusa Alcantara Gomes da Silva, Kátia Silene Oliveira e Silva, Andressa Torres Oliveira, Sandy Costa dos Santos, Lis Ferreira Barbosa, Regina Correia Lanzana Araújo da Silva, Cathleen Priscila Goes Bastos Araujo, Kélia das Graças de Paiva Macias Nakai, Nedson Sombra Gemaque, Isabela Xavier da Conceição Antunes, Bianca Caroline Gouvêa Trindade; et al. (Archives of Current Research International, 2025)
This study aimed to evaluate the scientific literature on the role of nursing in preventing adverse health events. Nurses play a central role in implementing safety practices, due to their continuous presence and direct contact with patients at different stages of care. A narrative review of the literature was conducted through a search in the BVS, PubMED, and Google Scholar databases, which selected texts published between 2019 and 2024. This review examines nursing performance in adverse event prevention, discussing key strategies, technological advancements, and the importance of continuous professional development. The events which can trigger negative consequences for patients, can be avoided and minimized through strategies and practices widely discussed in the scientific literature. Effective nursing interventions, vigilance, and adherence to best practices significantly reduce hospital-acquired infections, medication errors, and patient falls. Actions such as the promotion of healthy behaviours, early identification of health problems, the performance of preventive exams, adherence to safety protocols, patient education on healthy lifestyles, and involvement in public health initiatives have proven effective in reducing and preventing adverse events. It was possible to verify that Nursing plays a fundamental role in the identification and assessment of risks, implementation of preventive measures, and monitoring and control of adverse events. Contributions to nursing consist of highlighting the importance of nursing, as a category, as well as being constantly updated and trained with regard to patient safety.